Audit Informasi Terhadap Layanan Repositori Institusi Perpustakaan DPR RI - Faridan, Ridwan; Laksmi, Laksmi (Media Informasi, 2025)
The aim of the research is to identify information audit practices in institutional repository services at the DPR RI Library. The research uses qualitative methods with a case study approach. The result is that there are clearly organized procedures and task instructions, so that decision making is easy and activities run well. Collection selection has been adjusted to the information needs of users. The conclusion shows that the audit practice found that the flow of information was running well, supported by smooth division of work and communication between coordinators and staff.